Analysis of the Work of Under-Rail Gaskets in the Conditions of Railways of Uzbekistan - Abdurahimovich, Begmatov Pardaboy; Alisher o‘g‘li, Muminov Shahzod (European Journal of Life Safety and Stability (2660-9630), 2022)
The article examines the work of a sub-rail gasket made of rubber material and made an analysis of its different thicknesses in the regions of Uzbekistan.